2001
DOI: 10.1152/ajpcell.2001.281.6.c1743
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of cardiac and smooth muscle Ca2+channels (CaV1.2a,b) by protein kinases

Abstract: High voltage-activated Ca(2+) channels of the Ca(V)1.2 class (L-type) are crucial for excitation-contraction coupling in both cardiac and smooth muscle. These channels are regulated by a variety of second messenger pathways that ultimately serve to modulate the level of contractile force in the tissue. The specific focus of this review is on the most recent advances in our understanding of how cardiac Ca(V)1.2a and smooth muscle Ca(V)1.2b channels are regulated by different kinases, including cGMP-dependent pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

8
183
3
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 211 publications
(195 citation statements)
references
References 202 publications
8
183
3
1
Order By: Relevance
“…Thus, we hypothesise that PKC-δ may act on MAP kinase phosphorylation following C-peptide exposure. At the same time, activated PKC-δ and -ɛ could phosphorylate and activate other downstream target proteins such as Ca 2+ channels [41,42]. L-Type Ca 2+ channels have been reported to be positively modulated by novel PKC isoforms [41,43] and it is established that C-peptide is capable of eliciting increases in intracellular Ca 2+ concentration [2,5,6].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, we hypothesise that PKC-δ may act on MAP kinase phosphorylation following C-peptide exposure. At the same time, activated PKC-δ and -ɛ could phosphorylate and activate other downstream target proteins such as Ca 2+ channels [41,42]. L-Type Ca 2+ channels have been reported to be positively modulated by novel PKC isoforms [41,43] and it is established that C-peptide is capable of eliciting increases in intracellular Ca 2+ concentration [2,5,6].…”
Section: Discussionmentioning
confidence: 99%
“…At the same time, activated PKC-δ and -ɛ could phosphorylate and activate other downstream target proteins such as Ca 2+ channels [41,42]. L-Type Ca 2+ channels have been reported to be positively modulated by novel PKC isoforms [41,43] and it is established that C-peptide is capable of eliciting increases in intracellular Ca 2+ concentration [2,5,6]. In the present study we found that the Ca 2+ channel blockers verapamil and nifedipine abolished the effect of C-peptide on ERK1/2 phosphorylation, indicating that C-peptide stimulation results in an influx of Ca 2+ rather than in the release of intracellular Ca +2 stores.…”
Section: Discussionmentioning
confidence: 99%
“…Nitric oxide and cGMP-dependent kinase (PKG) have been traditionally viewed as mediators of vasodilation through effects on large conductance, Ca 2ϩ -activated potassium (BK) channels (26), VDCC (27,28), phospholamban (29), and IRAG inositol trisphosphate receptor-associated cGMP kinase substrate, as well as by decreasing the Ca 2ϩ sensitivity of the contractile process (30 -32). Recent evidence indicates that NO/ PKG can promote or inhibit vascular remodeling (33).…”
mentioning
confidence: 99%
“…Protein kinases, such as PKA, PKC, and PKG, may modulate function of I Ca,L channel [23,24] . Some studies have reported that hyposmotic swelling modulates function of ion channels by changing activities of protein kinases, such as PKC, tyrosine protein kinase [8,17,25,26] .…”
Section: Discussionmentioning
confidence: 99%
“…Experiments utilizing direct activators of PKC have also demonstrated a range of effects on I Ca,L [23,24] . In this research, we observed that PKC activator (PMA) decreased the basal I Ca,L ( Figure 6) and PKC inhibitor (BIM) prevented the biphasic effects of hyposmotic swelling on I Ca,L (Figure 7).…”
Section: Discussionmentioning
confidence: 99%